Becoming dishuman: thinking about the human through dis/ability. Issue 1 (2nd January 2016) - Goodley, Daniel; Runswick-Cole, Katherine
Abstract : In this paper, we seek to develop an understanding of the human driven by a commitment to the politics of disability, especially those of people with intellectual disabilities. Our position as family members and allies to people associated with this phenomenon of intellectual disability influences our philosophical conceptions and political responses. This has led us recently to develop a theory of dis/human studies which, we contend, simultaneously acknowledges the possibilities offered by disability to trouble, reshape and re-fashion the human (crip ambitions) while at the same time asserting disabled people's humanity (normative desires). We sketch out four dis/human considerations: (1) dis/autonomy, voice and evacuating the human individual; (2) dis/independence, assemblage and collective humanness; (3) dis/ability politics, self-advocacy and repositioning the human; and (4) dis/family: desiring the normal, embracing the non-normative. We argue that this feeds into the wider project of dis/ability studies, and we conclude that we desire a time when we view life through the prism of the dishuman (note, without the slash).